Developing Problem-Based Learning Modules on Petroleum Materials in Chemistry Learning - Ahmad, Fauziah; Murtihapsari, Murtihapsari; Rombe, Yunita Pare (JTK (Jurnal Tadris Kimiya), 2023)
The aim of this study is to investigate how to develop, validity, and practicality levels from the PBL-based module. The research is based on Research & Development (R&D) with a modified 4-D development model to 3-D covering define, design, and development stages. Data collection tools include observation, validation, worksheet, and questionnaires of studentsâ€™ responses to the chemistry modules. Based on the study results, it was identified that the modules developed to determine criteria eligibility, practicality, and response students of Problem-Based Learning on petroleum material. The material and media experts’ validation tests showed 0.851 and 0.726 (valid), respectively. The average practically percentage of modules for students is 77.52% with very practical criteria. The development of PBL-based chemistry modules on chemistry and the application of petroleum is expected to help students in learning chemistry.